1975
DOI: 10.1002/cpt1975173258
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of methadone in methadone maintenance

Abstract: Six detoxified opiate addicts housed in a closed metabolic ward received methadone in stepwise increasing doses of 10, 20, 40, and 80 mg/day during 1 month. Four were given 14C-methadone at the lowest dose and again at the highest dose. Of the subjects receiving radiomethadone, 2 excreted the major part of the radioactivity in urine and 2 about equally in urine and feces. In addition to methadone, 7 metabolites were isolated and identified in urine and 3 metabolites in feces. About 75% of the urinary and fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 5 publications
1
31
0
Order By: Relevance
“…Methadone is metabolized in the liver by the cytochrome P450 system and, more specifically, by the CYP3A4 isoform, which is involved in the metabolism of over 50% of the medical agents [33] . The wide interindividual variability [34][35][36] recorded, and the fact that CYP3A4 can be induced by several active principles [37] , may explain why a number of patients are undermedicated if a standard dose of methadone is used.…”
Section: Discussionmentioning
confidence: 99%
“…Methadone is metabolized in the liver by the cytochrome P450 system and, more specifically, by the CYP3A4 isoform, which is involved in the metabolism of over 50% of the medical agents [33] . The wide interindividual variability [34][35][36] recorded, and the fact that CYP3A4 can be induced by several active principles [37] , may explain why a number of patients are undermedicated if a standard dose of methadone is used.…”
Section: Discussionmentioning
confidence: 99%
“…1 (Sporkert and Pragst, 2000). P450-mediated p-hydroxylation of one of the aromatic rings has also been reported (Sullivan and Due, 1973;Anggård et al, 1975;Foster et al, 1999). Initial in vitro data suggested that CYP3A4 is the major isoform responsible for the in vivo clearance of methadone in humans (Iribarne et al, 1996;Iribarne et al, 1997).…”
Section: Introductionmentioning
confidence: 91%
“…Further investigations should also be enzyme induction and other adaptive changes on the metabolism of methadone [25,28,36,49,50]. Whether aimed at clarifying the roles of plasma binding and enantioselective kinetics [48], and the influence of autothese complexities present formidable obstacles to the 4 From population analysis with t 1/2,z as a primary parameter with a log-normal distribution staff of the Leeds Addiction Unit for their assistance.…”
Section: Pharmacokineticsmentioning
confidence: 99%